A fundamental analysis of stock valuation of Grameen Phone Limited and Robi Axiata Limited and recommending investing decisions - Mahtab, Juhayer (Brac University, 2024)
This internship report is submitted in partial fulfillment of the requirements for the degree of Bachelor of Business Administration, 2023.